Effect of Ca and RE additions on microstructures and tensile properties of AZ31 alloys. (23rd May 2018) - Fu, Li; Le, Qichi; Tang, Yan; Sun, Jingying; Jia, Yonghui; Song, Zetian
Abstract: Microstructures and tensile properties of AZ31 magnesium alloys with the same amount of Ca and RE (Gd + La) additions are investigated. The results show that Al2 Ca new phases form after adding Ca elements, Al2 Gd and Al11 La3 new phases form after adding Gd and La elements, and formations of Al-Ca and Al-RE phases could decrease Mg17 Al12 phases and refine grains. Al2 Ca and Al11 La3 phases are crushed into granules because of severe deformation during hot extrusion, while Al2 Gd phases are not. Room temperature (TR ) and 150 °C (T150°C ) tensile tests results reveal that both AZ31-1.5Ca and AZ31-1.5RE as-extruded alloys exhibit superior comprehensive tensile properties when compared to AZ31 as-extruded alloy, however, AZ31-1.5Ca as-extruded alloy could be a better choice in view of the costs. Textures images of as-extruded alloys indicate that 1.5 wt% Ca and RE additions affects little on textures of AZ31 as-extruded alloy, therefore, morphologies of second phases and average grain sizes are the leading cause of tensile properties of as-extruded alloys.